2021
DOI: 10.3390/ijgi10050298
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surface Water Availability under Climate Change Using Coupled SWAT-WEAP in Hongshui River Basin, China

Abstract: Climate change adversely affects the hydrological cycle at the basin level. This study integrated two models, the Soil and Water Assessment Tool (SWAT) for future climate prediction, and Water Evaluation and Planning (WEAP) for the simulation of water quantity in the Hongshui River Basin (HRB), to evaluate the impacts of climate change, which plays a significant role in the lives of inhabitants downstream of the basin. Downscaled monthly rainfalls and temperatures under four Representative Concentration Pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
3
5
0
1
Order By: Relevance
“…These results are in line with the findings by Touseef et al. (2021), which predict potential water shortages after 2050 over the Hongshui River Basin in China, and are more likely to happen under the high climate change emission scenario.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with the findings by Touseef et al. (2021), which predict potential water shortages after 2050 over the Hongshui River Basin in China, and are more likely to happen under the high climate change emission scenario.…”
Section: Discussionsupporting
confidence: 92%
“…Touch et al (2020) evaluated the effect of climate change on water availability in the Pursat River Basin in Cambodia, and the results showed that water availability will be declined in the future. Touseef et al (2021) also indicated that precipitation and streamflow may reduce in the future in the Hongshui River Basin in China. In the aforementioned studies, the findings generally revealed that climate change is likely to unequivocally influence water availability, and the climate change impact may vary across regions.…”
Section: Introductionmentioning
confidence: 99%
“…The Long Ashton Research Station Weather Generator (LARS-WG) model is applicable in water resources analysis as an efficient tool for the prediction of future climate variables [31,32]. One of the benefits of the water evaluation and planning (WEAP) model connected with the SWAT model is the spatiotemporal balancing of the water resources and water demand to optimize water resources management under current and future climate conditions [33,34].…”
Section: Introductionmentioning
confidence: 99%